Analyzing Curcumin Content using UV-Vis Spectrophotometry and TLC-Densitometry Methods: A Case Study in Curcuma Capsule Commercial Products - Rakhmawati, Rita; Anastacia, Laura; Hadi, Saptono (Chemistry Department, The University of Brawijaya, 2025)
Curcuma is a genus of plants commonly used in herbal medicine due to its benefits, primarily from the active compound curcumin. Accurate analytical methods are necessary to identify and quantify curcumin for quality control, especially in small-scale industries. This study compares spectrophotometry UV-visible and TLC-densitometry methods for analyzing Curcuma capsules from PT Rachmasari Group, a small-scale traditional medicine industry (UKOT) in Sukoharjo. The methods were evaluated based on linearity, LOD, LOQ, repeatability, intermediate precision, and accuracy. TLC-densitometry used a mobile phase of chloroform: methanol (95:5 v/v) and silica plates F254, while spectrophotometry used ethanol as the solvent. Both methods used a wavelength of 420 nm. Spectrophotometry showed better linearity (r2 = 0.9985) than TLC (r2 = 0.9847), while TLC-densitometry demonstrated higher sensitivity with lower LOD and LOQ values (1.2853 and 4.2845 μg/mL) compared to spectrophotometry (13.9261 and 46.4203 μg/mL). UV-Visible spectrophotometry exhibited superior repeatability (0.33 ± 0.02%) and intermediate precision (0.34 ± 0.01%) than TLC (1.86 ± 0.12% and 1.02 ± 0.88%). Accuracy ranged from 98.45–105.90% for spectrophotometry and 98.81–115.82% for TLC-densitometry. In conclusion, UV-Visible spectrophotometry is more precise, linear, and reliable overall, making it more suitable for curcumin quality control in small-scale herbal product industries.